2022
DOI: 10.3390/jcm11195817
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Microbiome and Cytokines in Healthy Implants and Peri-Implantitis of the Same Individuals

Abstract: Aim: To characterize the profile of submucosal microbiome and cytokine levels in peri-implant crevicular fluid (PICF) from clinically healthy implants and peri-implantitis in the same individuals. Material and Methods: A total of 170 patients were screened and, finally, 14 patients with at least one healthy implant and one peri-implantitis implant were included. Submucosal microbiota and cytokines from 28 implants were analyzed using 16S rRNA gene sequencing and multifactor assays, respectively. Correlations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
1
16
2
Order By: Relevance
“…The diversity, as it relates to the richness and evenness of microbiota, revealed that peri-implant sulci of peri-implantitis and control implants had a remarkable similarity, which is consistent with previous reports. [36][37][38] These findings were, however, in disagreement with previous reports suggesting Graphs show the mean relative abundances of each genus, which were calculated from all the samples within the respective categories (with >1% relative abundance). that peri-implantitis microbiota is more diverse than control implants.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The diversity, as it relates to the richness and evenness of microbiota, revealed that peri-implant sulci of peri-implantitis and control implants had a remarkable similarity, which is consistent with previous reports. [36][37][38] These findings were, however, in disagreement with previous reports suggesting Graphs show the mean relative abundances of each genus, which were calculated from all the samples within the respective categories (with >1% relative abundance). that peri-implantitis microbiota is more diverse than control implants.…”
Section: Discussioncontrasting
confidence: 98%
“…Other studies reported different predominant species of peri-implantitis core microbiomes than those found in this study. [36][37][38][39][40][41][42][43][44][45] At the diagnostic level, the results of the microbiome could vary due to the definition of peri-implantitis. 5 The diagnosis of peri-implantitis in this study was made by a trained periodontist and prosthodontist (H.S.…”
Section: Discussionmentioning
confidence: 99%
“…This can have significant implications for enhancing the quality of patient care. Looking towards the future, one particularly notable approach would involve the integration of the quantification of pro-inflammatory cytokines such as IL-17A, IL-6, IL-15, and matrix metalloproteinase 8 (MMP8), associated with the development of peri-implantitis, 47 complementing the SERS biochemical fingerprint of PICF, and affording a more comprehensive understanding of the inflammatory environment. The resulting complex set of heterogeneous and complex data will benefit from the use of advanced machine learning techniques, such as convolutional neural networks and deep learning.…”
Section: Discussionmentioning
confidence: 99%
“…During the peri‐implant healing process, the epithelial tissue has the function of covering the exposed connective tissue, forming a barrier similar to that of the junctional epithelium, while the connective tissue keeps the epithelium in position, preventing its apical migration 3,4 . If a bacterial infiltrate occurs and the installation of a local infectious and inflammatory process, several cytokines and interleukins and inflammatory mediators are expressed in the tissues, such as interleukin 6 and 8 (IL‐6 and IL‐8) 17 . Metalloproteinase type 3 (MMP‐3) is expressed by proliferating keratinocytes adjacent to the wound edge, which are in contact with an intact basement membrane 18 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 If a bacterial infiltrate occurs and the installation of a local infectious and inflammatory process, several cytokines and interleukins and inflammatory mediators are expressed in the tissues, such as interleukin 6 and 8 (IL-6 and IL-8). 17 Metalloproteinase type 3 (MMP-3) is expressed by proliferating keratinocytes adjacent to the wound edge, which are in contact with an intact basement membrane. 18 It regulates the rate of wound healing through its role in wound contraction.…”
mentioning
confidence: 99%